Impedância eletromecânica em heteroestruturas para determinação de transformações de fases em ligas de memória do forma - Silvestre, Alysson Domingos (2023)
Smart materials show spectacular intrinsic characteristics when externally stimulated and can promote significant changes in their initial state. In particular, SMAs (Shape Memory Alloys) have been widely discussed in scientific and technological works, as their peculiar characteristics of recovering their previously established shape when subjected to a thermomechanical or electromagnetic procedure, make them attractive for the most diverse uses and applications. However, to use them properly, it is necessary to understand the properties involved in the process that defines its main characteristic, phase transformation. Therefore, this work presents an investigation proposal for a method with a different operating principle, called (EMIH) Electromechanical Impedance in Heterostructure as an alternative tool to Differential Scanning Calorimetry (DSC) to measure phase transformation temperatures in SMAs alloys. The method uses a piezoelectric ceramic junction - lead zirconate titanate (PZT) with SMA metal. With this, equipment capable of providing thermal cycling in the form of heat to PZT/SMA samples (heterostructure) and its characterization is proposed. The investigation addresses samples of: Ni-Ti (Nickel, titanium), for two types of heat treatment, Ni-Ti-Nb (Nickel, titanium, Niobium), Co-Al-Ni (Copper, Aluminum, Nickel), in addition to steel, copper, and brass were analyzed. The proposed method was evaluated quantitatively through impedance magnitude and phase angle with different fixed frequencies and different heating and cooling rates, obtaining excellent results when compared to the DSC method. Heterostructure capacitance was also evaluated.